ALP (Accounting, Legal, Psychology) Devices as the Sustainability of Diforce Women's Lives (Case Study: Diforce Women Registered at the Medan High Religious Court) - Yenni Ramadhani Harahap; Roos Nelly; Amelia Alsa; Muslim, Muslim; Enika Diana Batubara; Hariyati Lubis; T. Elfira Rahmayati; TM. Adriansyah (Jurnal Ekonomi, 2024)
Sumatra Island has the highest population with the highest divorce rate in the last six years (katadata.co.id). This condition has an effect on women in force, such as the results of Soraya's research (2013) which states that the post-divorce impacts experienced by young women are psychological, economic, and social impacts that are felt to be negative and ostracized by the surrounding community. The use of ALP (Accounting, Legal, Psychology) devices can be used as an effort to carry out the sustainability of women's lives in force. The purpose of the research is to help women in force PA Medan Class IA (case: divorce lawsuit) to avoid as early as possible the negative impacts of post-divorce such as psychological, economic, legal blindness so that they are able to carry out their sustainability of life well and healthily through ALP (Accounting, Legal, Psychology) devices in an integrated manner in the form of procedures (Journaling). The research method used is descriptive method, field research, quasi-experiment; The data analysis method uses a non-equivalent control group design (non-equivalent pretest – posttest), meaning that this experiment was created with observations under artificial conditions where these conditions were created and regulated by the researcher. Results And Discussion study This is the categorization of research subject scores at the time of pretest and at the time of posttest . After being given treatment activities using the ALP Device through Journaling, it can be seen that there is an increase in the score of Diforce Women's Life Sustainability in research subjects in terms of financial health, legal literacy, and mental health (self-esteem and spiritual) as well as physical health. This means that this ALP device can be a new innovation in the world of education in the fields of accounting, law, psychology as a tool for recovering from depressed conditions when women experience post-divorce so that they can continue their lives much better such as financial health, legal literacy, and mental health (self-esteem and spiritual) as well as physical health .